Titanium: a review on exposure, release, penetration, allergy, epidemiology, and clinical reactivity - Fage, Simon W.; Muris, Joris; Jakobsen, Stig S.; Thyssen, Jacob P. (Contact dermatitis, 2016)
Summary Exposure to titanium (Ti) from implants and from personal care products as nanoparticles (NPs) is common. This article reviews exposure sources, ion release, skin penetration, allergenic effects, and diagnostic possibilities. We conclude that human exposure to Ti mainly derives from dental and medical implants, personal care products, and foods. Despite being considered to be highly biocompatible relative to other metals, Ti is released in the presence of biological fluids and tissue, especially under certain circumstances, which seem to be more likely with regard to dental implants. Although most of the studies reviewed have important limitations, Ti seems not to penetrate a competent skin barrier, either as pure Ti, alloy, or as Ti oxide NPs. However, there are some indications of Ti penetration through the oral mucosa. We conclude that patch testing with the available Ti preparations for detection of type IV hypersensitivity is currently inadequate for Ti. Although several other methods for contact allergy detection have been suggested, including lymphocyte stimulation tests, none has yet been generally accepted, and the diagnosis of Ti allergy is therefore still based primarily on clinical evaluation. Reports on clinical allergy and adverse events have rarely been published. Whether this is because of unawareness of possible adverse reactions to this specific metal, difficulties in detection methods, or the metal actually being relatively safe to use, is still unresolved.